INTERELASI PENDIDIKAN AGAMA ISLAM DAN POLITIK DI INDONESIA - Efendi, Dedi; Iswantir, Iswantir (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2023)
This article examines the reciprocal relationship of education, especially Islamic religious education and politics. The interrelation between the two is very close and cannot be separated, like two sides of a coin that are parallel and in the same direction. Politics on the one hand has the power to determine the direction of education, education on the other hand provides resources for politics. The interrelation between the two is sometimes good, sometimes bad depending on the ideology adopted by the political authorities at that time. The study of educational politics is very complex and comprehensive